Pengelolaan Lembaga Pendidikan Islam dalam Perspektif Manajemen Pendidikan - Muammar Idwin; Martin Kustati; Rezki Amelia (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the management of Islamic educational institutions from the perspective of educational management. Using the literature study method, this research examines various literatures related to strategic planning, organization, Islamic leadership, human resource management, and the implementation of holistic and integrated learning. The research results indicate that the management of Islamic educational institutions requires an integration between modern managerial principles and noble Islamic values, to create institutions that excel not only in academic aspects but also in character and moral development of students. Furthermore, the principles of accountability and transparency in supervision and evaluation are key factors in ensuring the sustainability and success of Islamic educational institutions. This research contributes to understanding the managerial concepts based on Islamic values in managing quality Islamic educational institutions.